Morphological Structure of the Body Setae as Mechanoreceptor on the Mesonotum of Telenomus remus Nixon (Hymenoptera, Platygastridae) - Wikantyoso, Bramantyo; Putra, Ichsan Luqmana Indra (Universitas Ahmad Dahlan, 2023)
Telenomus remus is parasitoid on many Lepidpoteran. Morphological analysis on T. remus is important to understand their behavior and assest the quality of parasitoid comes from the mass rearing process. However, the information of T. remus body setae cuticle characteristics were limited. This study aimed to explore the body setae on the mesonotum of of T. remus by using electron microscopy analysis and characterize their cuticle characterisics to infer the putative function of the body setae. The results showed structures that support the body setae on the mesonotum as mechanoreceptor. The structure included the long and dangling seta peg, a socket, and a gap between a socket and the base of the seta peg. The putative function related to the biology and behavior of T. remus were discussed.